A v-microalloyed ultra-high strength al-mg-si-cu alloy and a method for producing the same
Patent Information
- Application Number
- CN202510364235.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2026-09-29
AI Technical Summary
[0007]然而,上述专利中高强Al-Mg-Si-Cu系合金屈服强度范围为:屈服强度265~362MPa,抗拉强度为340~394MPa,延伸率为10%~11.4%
[0040]本发明在成分设计上,通过调整Mg、Si及Cu元素的含量,将合金Mg/Si比控制在1.1~1.7,在高Mg/Si比条件下,结合微量V元素的添加,引入新的AlMgV弥散相,并控制弥散相密度在1.5×1012~2.7×1012/m2,平均尺寸在350~500nm,实现了亚微米弥散相和纳米强化相的协同调控,提高材料力学性能;同时,Al-Mg-V弥散相在热变形过程中抑制晶界移动,减低晶粒长大和粗化速率,细化晶粒尺寸,在保证铝合金塑性的前提下,突破了6xxx系铝合金的强度限制,获得更高强度的新型6xxx系铝合金。峰时效态下合金屈服强度≥370MPa,抗拉强度≥420MPa,延伸率≥14%。而现有报道的高强Al-Mg-Si-Cu系铝合金板材屈服强度265~362MPa,抗拉强度为340~394MPa,延伸率为10%~11.4%。
Smart Images

Figure CN122833349A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum alloy technology, specifically relating to a V microalloyed ultra-high strength Al-Mg-Si-Cu alloy and its preparation method. Background Technology
[0002] Aluminum alloy sheets used in automotive bodies must possess high mechanical properties while also exhibiting good formability, weldability, and corrosion resistance. Currently, 6xxx series aluminum alloys are widely used in automotive outer panels due to their moderate strength, excellent plasticity, corrosion resistance, and surface quality. However, with the increasing emphasis on lightweighting and safety in automobiles, new requirements are being placed on the mechanical properties of 6xxx series aluminum alloys.
[0003] As a typical heat-treatable aluminum alloy, 6xxx series aluminum alloys primarily improve their strength through aging precipitation. Currently, the commonly used alloying approach involves increasing the content of Mg and Si elements and optimizing their ratio to promote the nucleation and precipitation of the main strengthening phase (Mg-Si phase), thereby enhancing precipitation strengthening. Alternatively, the introduction of some Cu and Zn elements can promote Mg-Si phase precipitation while simultaneously introducing new strengthening phases (Mg-Si-Cu and Mg-Zn phases), thus improving alloy strength. However, the relatively low solid solubility of the Mg-Si phase in the Al matrix somewhat limits its precipitation strengthening effect.
[0004] Chinese patent CN110760723A discloses an aluminum-magnesium-silicon erbium-zirconium alloy and a preparation process for improving its high-temperature mechanical properties. The alloy composition is: Mg: 0.8-1.2%, Si: 0.7-1.3%, Mn: 0.4-0.9%, Cu: 0.05-0.2%, Er: 0.01-0.4%, Zr: 0.01-0.4%, with the balance being Al. It is an Er and Zr composite microalloyed Al-Mg-Si alloy. The key feature is that rare earth elements Er and Zr are added to the aluminum alloy in a microalloying manner, which significantly improves the room temperature mechanical properties and high-temperature mechanical properties of the aluminum alloy, and significantly increases the room temperature tensile strength and elongation.
[0005] Chinese patent CN115323203A discloses a Cu and Sn composite microalloyed material for high-strength Al-Mg-Si alloys used in automotive bodies, its preparation process, and its application. This alloy comprises the following elements by mass percentage: Mg: 0.5–1.5 wt%, Si: 1.0–2.0 wt%, Cu: 0.4–1.0 wt%, Sn: 0.1–0.5 wt%, Mn ≤ 0.05 wt%, Fe ≤ 0.10 wt%, with the balance being Al. The composite addition of Cu and Sn elements inhibits the formation of clusters during the natural aging stage of the alloy and promotes the formation of clusters that can directly transform into the β″ phase. This enhances the age-hardening effect of the Al-Mg-Si alloy, improves its baking hardness, and solves the problem of insufficient baking hardening of Al-Mg-Si alloys used in automotive body panels after room temperature storage.
[0006] Chinese patent CN106480343A discloses a novel Al-Mg-Si alloy material with high strength and resistance to seawater corrosion, and its preparation method. The alloy material contains the following elements in the following mass percentages: Mg: 1.8-3.6 wt.%; Si: 1.6-3.3 wt.%; Mn: 0.45-0.65 wt.%; Cr: 0.25-0.35 wt.%; Zr: 0.15-0.3 wt.%; Ti: 0.2-0.3 wt.%; Ag: 0.2-0.5 wt.%; other impurities are individually ≤0.03 wt.% and the total is ≤0.1 wt.%, with the balance being aluminum. By appropriately controlling the content of Mg and Si in the alloy and the Mg / Si ratio, and by adding trace elements such as Mn, Cr, and Zr, the structure of harmful phases such as iron can be changed, their adverse effects eliminated, the recrystallization temperature and corrosion potential of the alloy increased, the grains refined, and the alloy strength and ductility improved. In addition, the addition of Ag can effectively enhance the heat treatment strengthening effect, increase the precipitation density of strengthening phases during aging, improve the mechanical properties of the alloy, change the atomic percentage of strengthening phase elements, reduce the potential difference between the precipitated phase and the matrix, and improve the corrosion resistance of the alloy.
[0007] However, the high-strength Al-Mg-Si-Cu alloys in the aforementioned patents have a yield strength range of 265–362 MPa, a tensile strength of 340–394 MPa, and an elongation of 10%–11.4%. Furthermore, the Er and Zr system elements used in these alloys to improve strength are relatively expensive, limiting their commercial application. To obtain aluminum alloys with higher strength and lower cost, and to meet the lightweight design requirements of the transportation sector for ultra-high-strength aluminum alloy sheets... Summary of the Invention
[0008] The purpose of this invention is to provide a V-microalloyed ultra-high strength Al-Mg-Si-Cu alloy and its preparation method. Without adding costly Er and Zr series elements, a higher strength aluminum alloy with excellent plasticity is obtained. The yield strength of the aluminum alloy is ≥370MPa, tensile strength is ≥420MPa, and elongation is ≥14%, which meets the lightweight design and safety requirements of future transportation fields.
[0009] To achieve the above objectives, the technical solution of the present invention is as follows:
[0010] A V-microalloyed ultra-high strength Al-Mg-Si-Cu alloy has the following composition by mass percentage: Mg: 1.2-2.0 wt.%, Si: 1.0-1.5 wt.%, Cu: 0.5-1.5 wt.%, Zn: 0.1-0.5 wt.%, Mn: 0.2-0.4 wt.%, V: 0.05-0.4 wt.%, Fe≤0.2 wt.%, with the remainder including Al and unavoidable impurities. Furthermore, all of the above elements must simultaneously satisfy: 1.1≤Mg / Si≤1.7.
[0011] Furthermore, the remainder consists of Al and unavoidable impurities.
[0012] The aluminum alloy described in this invention has a yield strength ≥370MPa, a tensile strength ≥420MPa, and an elongation ≥14%.
[0013] The aluminum alloy microstructure of this invention consists of fine equiaxed crystals with a grain size of 14–18 μm; and uniformly distributed nano-precipitates and dispersed phases are present in the microstructure, wherein the dispersed phase is an AlMgV phase with a dispersion density of 1.5 × 10⁻⁶. 12 ~2.7×10 12 / m 2 The average size is 350–500 nm; the nano-precipitated phases are β″ and Q′ phases, with a density of 5.5 × 10⁻⁶. 14 ~7.5×10 14 / m 2 The average length is 10–15 nm.
[0014] The ultra-high strength Al-Mg-Si-Cu alloy micro-alloyed in this invention has the following compositional design:
[0015] Mg: In this invention, the content of Mg and Si elements determines the content of the β-Mg2Si phase in 6xxx series aluminum alloys, and also determines the strengthening effect of the main strengthening phase—the β phase and its metastable phase. However, when the β phase content is too high, it is difficult for it to completely dissolve back into the matrix after high-temperature solution treatment. Therefore, it is necessary to control the total content of the above two elements. In addition, in Al-Mg-Si-Cu alloys, increasing the Mg / Si ratio of the alloy can accelerate the aging response rate of the alloy. This is because excess Mg can reduce the solid solubility of the β phase in the Al matrix, making it easier for the supersaturated solid solution to precipitate the strengthening phase during aging. Therefore, in this invention, the Mg content is controlled at 1.2–2.0 wt.%, and 1.1 ≤ Mg / Si ratio ≤ 1.7.
[0016] Si: Adding Si can form effective reinforcing phases such as Mg-Si and Mg-Si-Cu with Mg and Cu, but the relatively high Mg content reduces the solid solubility of Si in the Al matrix. Furthermore, excess Si can also combine with Fe to form αAlFeSi, βAlFeSi, and Al... 15 Iron-rich intermetallic compounds of the (Fe,Mn)3Si2 phase reduce the material's deformability. Therefore, in this invention, the Si content is controlled at 1.0–1.5 wt.%.
[0017] Cu: In the system of this invention, under the premise of excess Mg content, the addition of some Cu can change the aging precipitation sequence of the β phase during aging, introduce a new strengthening phase -Q phase and its metastable phase, forming a two-phase strengthening effect and improving the peak aging intensity of the alloy; in addition, the addition of Cu can also improve the aging response rate of the alloy and shorten the time required for peak aging treatment. Therefore, the Cu content is set to 0.5~1.5 wt.%.
[0018] Zn: Generally, Zn does not directly participate in the precipitation process of β and Q phases in 6xxx series aluminum alloys. Adding a small amount of Zn to 6xxx series aluminum alloys can improve the stability of Mg-Si clusters during aging or pre-aging treatments, thereby enhancing aging response behavior and mechanical properties. Therefore, this invention controls the Zn content to 0.1–0.5 wt.%.
[0019] Mn: As a commonly used trace element in aluminum alloys, adding a small amount of Mn can improve the morphology of the Fe-rich phase, transforming it from lath-like to spherical, thus improving the alloy's plasticity. Therefore, in this invention, the Mn content is controlled at 0.2–0.4 wt.%.
[0020] V: Adding trace amounts of V to Al-Mg alloys, controlling the ratio of 1.1 ≤ Mg / Si ≤ 1.7, can generate a new dispersed strengthening phase – AlMgV phase – under high Mg / Si ratio conditions, and the density of the strengthening phase can be controlled at 1.5 × 10⁻⁶. 12 ~2.7×10 12 / m 2 The average size is controlled between 350 and 500 nm. This phase can effectively pin grain boundaries during hot rolling, preventing grain growth and coarsening. While refining the grain size, it also improves the strength of the sheet by employing a composite strengthening method of dispersion strengthening and precipitation strengthening. Therefore, the V content is controlled between 0.05 and 0.4 wt.% in this invention.
[0021] Fe: Fe is a common impurity element in aluminum alloys. Its solid solubility in the Al matrix is very low, and it readily forms coarse intermetallic compounds with Si, increasing the heat treatment pressure of the alloy and reducing the plasticity of the sheet. Therefore, strict control is required. Thus, this invention controls the Fe content to ≤0.2 wt.%.
[0022] This invention, through rational design and optimization of the content of Mg, Si, and Cu elements, and by increasing the Mg / Si ratio of the alloy to 1.1–1.7, enhances the nucleation driving force of the strengthening phase (β phase and its metastable phase), promoting its precipitation. Furthermore, by adding trace amounts of V, an Al-Mg-V dispersed phase is formed in the matrix after homogenization treatment. On one hand, this phase pins grain boundary movement during hot working, inhibiting grain growth and coarsening, refining the alloy grain size, and controlling the microstructure to be fine equiaxed crystals with a grain size of 14–18 μm. On the other hand, a combination of dispersion strengthening and precipitation strengthening is employed, with the dispersed phase density controlled at 1.5 × 10⁻⁶. 12 ~2.7×10 12 / m 2 The average size is controlled within 350–500 nm, improving the alloy strength and breaking through the existing strength range of Al-Mg-Si-Cu alloys. The alloy yield strength at peak aging is ≥370 MPa, tensile strength is ≥420 MPa, and elongation is ≥14%, which is superior to the Al-Mg-Si-Cu aluminum alloy plates reported previously (yield strength range of 265–362 MPa, tensile strength of 340–397 MPa, and elongation of 10%–11.4%).
[0023] The method for preparing the V-microalloyed ultra-high strength Al-Mg-Si-Cu alloy of the present invention includes the following steps:
[0024] 1) Plates are obtained through smelting, casting, homogenization heat treatment, hot rolling, and cold rolling.
[0025] The homogenization heat treatment temperature is 545–560℃, the homogenization heat treatment holding time is 16–24 h, and the heating / cooling rate is 0.5–1.0℃ / min.
[0026] The total deformation during hot rolling is 85-90%, and the hot rolling temperature is 545-560℃.
[0027] 2) The cold-rolled sheet is solution treated and then water-quenched;
[0028] 3) Timeliness processing
[0029] After solution treatment and quenching, the sheet metal is subjected to aging treatment. The solution treatment temperature is 555-570℃, the solution treatment time is 0.5-1.5h, the aging treatment temperature is 150-185℃, and the aging treatment holding time is 4-24h.
[0030] Preferably, in step 1), high-purity aluminum, pure magnesium, pure zinc, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-V master alloy, and Al-Fe master alloy are used as raw materials.
[0031] First, high-purity aluminum is completely melted and heated to 760–780°C. Al-V and Al-Fe master alloys are added, and after the master alloys are completely melted, the melt is cooled to 740–760°C. Al-Cu and Al-Mn master alloys are added, and after they are fully melted, the melt is cooled to 730–740°C. Pure magnesium and pure zinc are added, and the temperature is maintained for 10–15 minutes. Then, a refining agent is added, and after it reacts fully with the melt, a slag remover is added, and the temperature is maintained at 720–740°C for 10–15 minutes. Finally, a refining agent is added, and the temperature is maintained for 2–5 minutes before casting to obtain an ingot.
[0032] The slag remover is a sodium-free slag remover, and its addition amount is 0.30 to 0.40 wt.% of the melt mass;
[0033] The refining agent used is Al-5Ti-1B, and its addition amount is 0.05 to 0.1 wt.% of the melt mass.
[0034] Preferably, in step 1), the cold rolling deformation is ≥65%.
[0035] Preferably, the casting temperature is 720–740°C.
[0036] In the process design of this invention:
[0037] The homogenization heat treatment temperature is 545–560℃, and the holding time is 16–24 h. The heating / cooling rate is 0.5–1.0℃ / min. By controlling the homogenization heat treatment temperature and cooling rate, the dispersed precipitation of the submicron AlMgV phase is ensured, which can effectively suppress the recrystallization process, refine the grains, and improve the plasticity of the material during subsequent hot deformation.
[0038] The solution temperature is 555–570℃ and the solution time is 0.5–1.5h. During the solution treatment, high temperature and long temperature holding are used to ensure that effective strengthening elements such as Mg, Si, Cu and Zn are fully dissolved back into the matrix, promote the synergistic precipitation of various nano-precipitates, and improve the strength of the alloy.
[0039] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0040] In terms of composition design, this invention controls the Mg / Si ratio of the alloy to be between 1.1 and 1.7 by adjusting the contents of Mg, Si, and Cu. Under high Mg / Si ratio conditions, a new AlMgV dispersed phase is introduced by adding trace amounts of V, and the density of the dispersed phase is controlled at 1.5 × 10⁻⁶. 12 ~2.7×10 12 / m 2 With an average size of 350–500 nm, the Al-Mg-V dispersed phase achieves synergistic regulation of submicron dispersed phases and nano-reinforcing phases, improving the mechanical properties of the material. Simultaneously, the Al-Mg-V dispersed phase inhibits grain boundary movement during hot deformation, reduces grain growth and coarsening rates, and refines grain size. While ensuring the plasticity of the aluminum alloy, it breaks through the strength limitations of 6xxx series aluminum alloys, obtaining a new type of 6xxx series aluminum alloy with higher strength. At peak aging, the alloy exhibits a yield strength ≥370 MPa, a tensile strength ≥420 MPa, and an elongation ≥14%. In contrast, existing reports of high-strength Al-Mg-Si-Cu series aluminum alloy plates show yield strengths of 265–362 MPa, tensile strengths of 340–394 MPa, and elongations of 10%–11.4%.
[0041] Based on the composition design, this invention optimizes the homogenization heat treatment, rolling process, and solution-aging treatment process, and follows the existing commercial 6xxx series aluminum alloy production process and flow. By controlling the composition and distribution of submicron dispersed phase and nano-reinforcing phase, the produced sheet has good surface quality and fine grain size, achieving an excellent match between high strength and excellent plasticity. It has certain guiding significance for the development, processing and application of new ultra-high strength 6xxx series aluminum alloy automotive body outer panels. Attached Figure Description
[0042] Figure 1 These are macroscopic images of hot-rolled and cold-rolled aluminum alloy sheets in Embodiment 6 of the present invention;
[0043] Figure 2 This is a grain morphology diagram of the aluminum alloy material in Embodiment 6 of the present invention;
[0044] Figure 3 This is a typical dispersed phase in the homogenized state of aluminum alloy material obtained in Example 6 of the present invention;
[0045] Figure 4 This is a typical strengthening phase in the aged state of the aluminum alloy material obtained in Example 6 of the present invention;
[0046] Figure 5 These are microstructure images of aluminum alloy materials obtained in Comparative Example 1 of this invention;
[0047] Figure 6 This is a grain size distribution diagram of the aluminum alloy material obtained in Comparative Example 1 of the present invention;
[0048] Figure 7 This is a comparison chart of the yield strength and elongation after fracture of the aluminum alloy material obtained in the embodiments of the present invention with the high-strength Al-Mg-Si-Cu aluminum alloys reported in patents (CN110760723A, CN115323203A and CN106480343A). Detailed Implementation
[0049] The present invention will be further described below with reference to the embodiments and accompanying drawings.
[0050] The aluminum alloy composition described in the embodiments and comparative examples of the present invention is shown in Table 1, the process parameters of the embodiments and comparative examples of the present invention are shown in Table 2, and the properties of the aluminum alloys obtained in the embodiments and comparative examples of the present invention are shown in Table 3.
[0051] Figure 1 These are microstructure images of the aluminum alloy material obtained in Example 6 of this invention. Figure 2 This is a grain size distribution diagram of the aluminum alloy material obtained in Example 6 of the present invention. As can be seen from the image, the grain size of the material is small, with an average size of 15.3 μm.
[0052] Figure 3 This is a typical dispersed phase in the homogenized state of the aluminum alloy material obtained in Example 6 of the present invention. Figure 4 This is a typical strengthening phase in the peak aging state of the aluminum alloy material obtained in Example 6 of this invention. As can be seen from the picture, a large number of submicron dispersed phases - AlMgV phase and high-density nano-strengthening phases (β″ phase and Q′ phase) are precipitated in the matrix, which improves the mechanical properties of the plate. Compared with the high-strength 6xxx series aluminum alloy plate reported in the patent, the mechanical properties of the material are greatly improved.
[0053] Figure 5 and Figure 6These are, respectively, microstructure images and grain size distribution diagrams of the aluminum alloy material obtained in Comparative Example 1 of this invention, and are compared with... Figure 1 , 2 The comparison revealed that, due to the lower density of the dispersed phase in Comparative Example 1, the grain size was significantly coarser than that in Example 6, with the average size increasing from 15.3 μm to 24.1 μm.
[0054] Figure 7 This is a comparison chart of the yield strength and elongation after fracture of the aluminum alloy material obtained in the embodiments of the present invention with that reported in patents (CN110760723A, CN115323203A and CN106480343A). The comparison shows that the V-microalloyed high-strength Al-Mg-Si-Cu alloy described in this invention has higher strength and better plasticity.
[0055] As shown in Table 3, after solution treatment and aging, the alloy designed in this invention exhibits a yield strength of 370–385 MPa, a tensile strength of 425–440 MPa, and an elongation of 14.5%–17%. Overall, the alloy achieves a yield strength ≥370 MPa, a tensile strength ≥420 MPa, and an elongation ≥14%, which is superior to existing Al-Mg-Si-Cu aluminum alloy sheets. This invention develops a novel V-microalloyed ultra-high-strength Al-Mg-Si-Cu alloy and its preparation method, addressing the need for ultra-high-strength 6xxx series aluminum alloy sheets in the lightweight design requirements of the transportation sector.
[0056] In Comparative Example 1, no V element was added to the alloy, resulting in a larger grain size and almost no dispersed phase in the matrix. Therefore, the peak aging state intensity of this alloy was relatively low.
[0057] In Comparative Example 2, no V element was added to the alloy, and the Mg / Si ratio was low, only 0.88. This resulted in a larger grain size, no dispersed phase precipitation, and a lower density of nano-precipitates. Ultimately, the alloy in Comparative Example 2 exhibited significantly lower strength and plasticity than the examples.
[0058] In Comparative Example 3, V was added to the alloy, but the Mg / Si ratio was relatively low, at 0.91. This reduction in the Mg / Si ratio to 0.91 resulted in a decrease in excess Mg content in the matrix due to the nucleation and growth process of the nano-precipitates, limiting the formation of the AlMgV dispersed phase and weakening the grain refinement effect and the promoting effect on the nano-precipitates. Ultimately, the densities of the dispersed and precipitated phases in this alloy decreased to 0.83 × 10⁻⁶. 12 / m 2 and 5.59×10 12 / m 2 The strength and plasticity of the sheet material were lower than those of the example.
[0059] This invention, through the rational design and control of the content of Mg, Si, and Cu elements, and the addition of trace amounts of V element, combined with homogenization treatment and solution-aging treatment, introduces a high-density precipitation-strengthening phase (β″ phase and Q′ phase) and a submicron dispersed phase—AlMgV phase—into the Al matrix. By employing a combination of dispersion strengthening and precipitation strengthening, the strength limitations of Al-Mg-Si-Cu alloys are overcome. Simultaneously, the AlMgV dispersed phase effectively inhibits grain boundary movement during hot deformation, reduces grain growth and coarsening rates, effectively refines the grain size of the sheet material, and improves the alloy's plasticity. This invention addresses the need for ultra-high strength 6xxx series aluminum alloy sheets in the lightweight design requirements of the transportation sector, providing a new solution for the design and development of novel ultra-high strength aluminum alloys.
[0060] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
[0061]
[0062]
[0063]
Claims
1. A V microalloyed ultra-high strength Al-Mg-Si-Cu alloy, the composition of which is as follows by mass percentage: Mg: 1.2-2.0 wt.%, Si: 1.0-1.5 wt.%, Cu: 0.5-1.5 wt.%, Zn: 0.1-0.5 wt.%, Mn: 0.2-0.4 wt.%, V: 0.05-0.4 wt.%, Fe≤0.2 wt.%, the remainder including Al and unavoidable impurities, and the above elements also need to simultaneously satisfy: 1.1≤Mg / Si≤1.
7.
2. The V-microalloyed ultra-high strength Al-Mg-Si-Cu alloy as described in claim 1, characterized in that, The remainder consists of Al and unavoidable impurities.
3. The V-microalloyed ultra-high strength Al-Mg-Si-Cu alloy as described in claim 1 or 2, characterized in that, The aluminum alloy microstructure consists of fine equiaxed crystals with a grain size of 14–18 μm; and uniformly distributed nano-precipitates and dispersed phases are present in the microstructure, wherein the dispersed phase is an AlMgV phase with a density of 1.5 × 10⁻⁶. 12 ~2.7×10 12 / m 2 The average size is 350–500 nm; the nano-precipitated phases are β″ and Q′ phases, with a density of 5.5 × 10⁻⁶. 14 ~7.5×10 14 / m 2 The average length is 10–15 nm.
4. The ultra-high strength Al-Mg-Si-Cu alloy with V microalloying as described in claim 1, 2, or 3, characterized in that, The aluminum alloy has a yield strength ≥370MPa, a tensile strength ≥420MPa, and an elongation ≥14%.
5. The method for preparing the V-microalloyed ultra-high strength Al-Mg-Si-Cu alloy as described in any one of claims 1 to 4, characterized in that, Includes the following steps: 1) Plates are obtained through smelting, casting, homogenization heat treatment, hot rolling, and cold rolling. The homogenization heat treatment temperature is 545–560℃, the homogenization heat treatment holding time is 16–24 h, and the heating / cooling rate is 0.5–1.0℃ / min. The total deformation during hot rolling is 85%–90%, and the hot rolling temperature is 545–560℃. 2) The cold-rolled sheet is solution treated and then water-quenched; 3) Timeliness processing After solution treatment and quenching, the sheet metal is subjected to aging treatment. The solution treatment temperature is 555-570℃, the solution treatment time is 0.5-1.5h, the aging treatment temperature is 150-185℃, and the aging treatment holding time is 4-24h.
6. The preparation method according to claim 5, characterized in that, In step 1), high-purity aluminum, pure magnesium, pure zinc, Al-Si master alloy, Al-Cu master alloy, Al-Mn master alloy, Al-V master alloy, and Al-Fe master alloy are used as raw materials. First, high-purity aluminum is completely melted and heated to 760–780°C. Al-V and Al-Fe master alloys are added, and after the master alloys are completely melted, the melt is cooled to 740–760°C. Al-Cu and Al-Mn master alloys are added, and after they are fully melted, the melt is cooled to 730–740°C. Pure magnesium and pure zinc are added, and the temperature is maintained for 10–15 minutes. Then, a refining agent is added, and after it reacts fully with the melt, a slag remover is added, and the temperature is maintained at 720–740°C for 10–15 minutes. Finally, a refining agent is added, and the temperature is maintained for 2–5 minutes before casting to obtain an ingot. The slag remover is a sodium-free slag remover, and its addition amount is 0.30 to 0.40 wt.% of the melt mass; The refining agent used is Al-5Ti-1B, and its addition amount is 0.05 to 0.1 wt.% of the melt mass.
7. The preparation method according to claim 5, characterized in that, The casting temperature is 720–740℃.
8. The preparation method according to claim 5, characterized in that, In step 1), the cold rolling deformation is ≥65%.
Citation Information
Patent Citations
Novel Al-Mg-Si alloy material high in strength and resistant to seawater corrosion and preparation method thereof
CN106480343A
Aluminum, magnesium, silicon, erbium and zirconium alloy and preparing technology for improving high-temperature mechanical performance
CN110760723A
Cu and Sn composite micro-alloyed material of Al-Mg-Si alloy for high-strength automobile body and preparation process and application of Cu and Sn composite micro-alloyed material
CN115323203A